17β-Hydroxysteroid dehydrogenase type 10 predicts survival of patients with colorectal cancer and affects mitochondrial DNA content. Issue 1 (28th April 2016) - Amberger, Albert; Deutschmann, Andrea J.; Traunfellner, Pia; Moser, Patrizia; Feichtinger, René G.; Kofler, Barbara; Zschocke, Johannes
Highlights: We examined expression of HSD10 in colorectal cancer. HSD10 is an independent prognostic marker for survival. HSD10 expression correlates with mitochondrial DNA content in cancer. Decreased HSD10 expression causes mitochondrial DNA depletion in cancer cells. Abstract: Mitochondrial energy production is reduced in tumor cells, and altered mitochondrial respiration contributes to tumor progression. Synthesis of proteins coded by mitochondrial DNA (mtDNA) requires the correct processing of long polycistronic precursor RNA molecules. Mitochondrial RNase P, composed of three different proteins (MRPP1, HSD10, and MRPP3), is necessary for correct RNA processing. Here we analyzed the role of RNase P proteins in colorectal cancer. High HSD10 expression was found in 28%; high MRPP1 expression in 40% of colorectal cancers, respectively. Expression of both proteins was not significantly associated with clinicopathological parameters. Survival analysis revealed that loss of HSD10 expression is associated with poor prognosis. Cox regression demonstrated that patients with high HSD10 tumors are at lower risk. High HSD10 expression was significantly associated with high mtDNA content in tumor tissue. A causal effect of HSD10 overexpression or knock down with increased or reduced mtDNA levels, respectively, was confirmed in tumor cell lines. Our data suggest that HSD10 plays a role in alterations of energy metabolism by regulating mtDNA content in colorectal carcinomas, and HSD10 protein analysis may be of prognostic value.